Sensitivity of streamflow and nutrient loads to changes in leaf area index and soil organic carbon in a sub-tropical catchment subject to climate change - Deng, Chao; Zhang, Hong; Hamilton, David P. (Journal of hydrology. Regional studies, 2024)
The Upper Nerang River Catchment located in South-East Queensland (SEQ), Australia. The Soil Water Assessment Tool (SWAT) model was applied to Upper Nerang River Catchment to test the sensitivity of catchment runoff and water quality to changes in Leaf Area Index (LAI) and Soil (topsoil) Organic Carbon (SOC) associated with climate change. These parameters are normally considered to be stationary in hydrological models, potentially constraining the accuracy of these models for catchment simulation under future climate scenarios. LAI decreased by 0.4% to 16.9% and SOC by 5.9 to 11.6%, depending on land cover, future period, and emission scenario. Climate change scenarios showed an increase in extreme flows compared with a baseline (recent historical) case and were characterised by reduced return period and greater magnitude of discharge. Changes in LAI and SOC have the potential to mitigate these changes and may reduce loads of SS, TN and TP under future climate change scenarios. The findings of this study indicate that incorporating changes in LAI and SOC into hydrological models is important for modelling the catchment response to climate change. Furthermore, LAI and SOC could be managed to mitigate impacts of climate change on streamflow and losses of SS, TN and TP from catchment soils to receiving waters. [Display omitted] •Climate change decreases the leaf-area-index (LAI) of vegetation cover and soil organic carbon (SOC) in topsoil.•Climate change brings more extreme flows with high return periods in terms of their magnitudes.•Variations in LAI and SOC relieve magnitude changes of extreme flows with high return periods and result in less catchment loads under future climate change conditions.